Aromaterapi Lavender Sebagai Terapi Alternatif Dalam Mengurangi Mual Muntah Pada Ibu Hamil Trimester Pertama - Ety Diana Sulistyawati; Rahma Fauziyah (Jurnal Ners, 2025)
Nausea and vomiting are common problems faced by pregnant women in the first trimester, which can disrupt their activities, nutritional intake, and quality of life. Non-pharmacological methods, such as lavender aromatherapy, are safe and easy to use because pharmacological treatments often cause side effects. Lavender contains linalool and linalyl acetate, which are calming and work by stimulating the brain's limbic system, which helps reduce pain. The purpose of this study was to determine the effectiveness of lavender aromatherapy in reducing vomiting and nausea during the first trimester of pregnancy in Kejayan Community Health Center, Pasuruan Regency. This study used a one-group pretest-posttest design with 32 consecutively selected research subjects. The intervention involved inhaling three drops of lavender oil on a sterile cotton swab for approximately ten minutes or more. This was done twice daily for 7 days. Before and after the intervention, nausea and vomiting were measured using the PUQE-24 instrument. With a p-value of 0.000, the results showed a significant decrease from moderate (59.4%) and severe (40.6%) to a predominantly mild category (84.4%). This research found that lavender aromatherapy can help pregnant women in the first trimester reduce their vomiting and can be recommended as a non-pharmacological treatment in community health centers.